2005
DOI: 10.1111/j.1745-7254.2005.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for gabapentin in neuroprotection of central nervous system in streptozotocine-induced diabetic rats1

Abstract: Aim: To investigate the effect of gabapentin on neural [neuron-specific enolase (NSE)] and glial markers [glial fibrillary acidic protein (GFAP) and S100B] in different brain regions of diabetic rats. Methods: Diabetes was induced by a single intraperitoneal injection of streptozotocine (50 mg/kg body weight). Rats in one diabetic group received gabapentin (50 mg·kg ) and rats in the other diabetic group received vehicle only for 6 weeks. The levels of GFAP, S100B, and NSE were determined by immunoblotting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 32 publications
6
38
0
Order By: Relevance
“…These results confirmed the previous reports that streptozotocin-induced diabetes was accompanied by an increased generation of reactive species. It is also suggested that the antioxidant compounds may have beneficial effects against the complications of diabetes mellitus [3436]. …”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed the previous reports that streptozotocin-induced diabetes was accompanied by an increased generation of reactive species. It is also suggested that the antioxidant compounds may have beneficial effects against the complications of diabetes mellitus [3436]. …”
Section: Discussionmentioning
confidence: 99%
“…These studies support increased MDA levels during diabetes and protective effects of bosentan. The increase in lipid peroxidation, on the other hand, leads to a decrease in a very important endogenous antioxidant substance, like glutathione [64,65]. Glutathione was found to be low in the diabetic rat groups in our study.…”
Section: Discussionmentioning
confidence: 70%
“…It affects all classes of macromolecules (sugar, lipid, protein and DNA), leading inevitably to neuronal dysfunction (Moreira et al, 2005). Baydas et al (2005) has reported that STZ causes glial and neuronal cell death in animal models for diabetes.…”
Section: Discussionmentioning
confidence: 99%